Esteroides produzidos por Penicillium herquei, um fungo endofítico isolado dos frutos de Melia azedarach (Meliaceae) Steroids produced by Penicillium herquei, an endophytic fungus isolated from the fruits of Melia azedarach (Meliaceae) - Andrey Moacir do Rosario Marinho; Patrícia Santana Barbosa Marinho; Edson Rodrigues Filho (Química Nova, 2009)
Six compounds comprising the groups of steroids, the ergosterol, the ergosterol peroxide, the cerevisterol, the neociclocitrinols, the ergosta-4,6,8(14),22-tetraen-3-one, the 25-hydroxy-ergosta-4,6,8(14),22-tetraen-3-one, were isolated from Penicillium herquei fungus obtained from Melia azedarach. The structures were identified by spectral methods of RMN 1D and 2D and MS.